The violin : a social history of the world's most versatile instrument - Schoenbaum, David (New York, NY : W.W. Norton & Company, 2013)
The life, times, and travels of a remarkable instrument and the people who have made, sold, played, and cherished it.
Making it. A star is born ; The golden age ; Over the hills and far away ; The road not taken ; Back to the future ; Last but not least -- Selling it . Paying the price ; The French connection ; The Ritz of violin shops ; From modern to postmodern ; "Fiddle, n. A swindle. orig. U.S." ; Violin cases -- Playing it. Learning how ; Players in general ; Players in particular ; Founding fathers ; How to get to Carnegie Hall ; Race, class, and gender ; Business and politics -- Imagining it. Still pictures worth a thousand words ; Poetry ; Prose ; Moving pictures worth a thousand words.
Includes bibliographical references and index.
Keywords: Violin; Violin -- History